Outcome of Dengue infection in pregnancy at a tertiary care hospital in India - Raza, Naimah; Dhungat, Nitin P. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Dengue is one of the most important mosquito-borne diseases in India. This study was done to study the course of dengue infection in pregnant women, its effects, foeto-maternal outcome, and associated complications. Methods: Clinical, laboratory findings, and maternal/foetal outcome were collected from patients with confirmed dengue infections in pregnancy treated at a tertiary care hospital in India, during a 6-month period. Results: A total 12 seropositive cases of dengue infection in pregnancy were diagnosed during the study period. Thrombocytopenia coupled with rising haematocrit were seen in all cases. Prophylactic platelet transfusion was not necessary in any of the cases without bleeding manifestation. Three patients developed severe dengue with some complication requiring extra measures, including a case of dengue encephalitis which responded to supportive treatment. One case of intra-uterine foetal demise and multi-organ failure leading to maternal death was seen. Perinatal outcomes of the other cases were satisfactory. Conclusions: Dengue in pregnancy requires early diagnosis and treatment. A high index of clinical suspicion is essential in any pregnant woman with fever, especially in endemic areas. Further studies are necessary as evidence-based data in the management of dengue in pregnancy is inadequate.